Vulnerability of Mediterranean grasslands to climate change: What can we learn from a long-term experiment ? - Henkin Z.; Perevolotsky A.; Sternberg M. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
Species diversity in Mediterranean grasslands could be seriously affected in the proximate future by significant changes in climate, as predicted by climate change models for the Mediterranean basin. These models forecast a reduction in precipitation, changes in seasonal rainfall distribution and a decrease in predictability. These changes can also affect the structure, production and composition of Mediterranean grasslands, particularly those that serve as rangelands. Here we present a long-term study (16 years) in Mediterranean grassland in Israel that aimed to evaluate the responses of plant species, plant functional groups and the plant community to different management regimes of cattle grazing. We examined the effects of precipitation change on the structure of the herbaceous community in order to understand the potential role of climate change. The results showed: (i) a decrease in peak standing biomass with decreasing annual rainfall; (ii) rainfall distribution and quantity played an important role in determining species composition -dry years favoured thistles and crucifers while wet years favoured legumes; (iii) grazing significantly reduced the cover of tall grasses; and (iv) that as yearly rainfall increased, stocking density had an additional negative effect on species diversity. Despite significant changes in rainfall amount and cattle grazing pressure along the studied period, the studied Mediterranean grassland showed a highly resilient response to all environmental variations. The perennial herbaceous component of these communities buffers against drastic changes in community structure and causes the Eastern-Mediterranean grassland to become potentially less vulnerable to climate change.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)